Miscellany/Mélanges - Besterman, T (Voltaire Foundation, 2017)
Sylvia Vance, History as dramatic reinforcement: Voltaire's use of history in four tragedies set in the middle ages Diderot, Réflexions sur le courage des femmes, texte inconnu (1745) identifié et présenté par J. Th. de Booy Henri Mydlarski, Vauvenargues, juge littéraire de son siècle Terence Murphy, Jean Baptiste René Robinet: the career of a man of letters